Physio-mechanical properties of aluminium metal matrix composites reinforced with Al2O3 and SiC - Debnath, Sujan; Oo, Zeya; Rahman, Muhammad Ekhlasur; Maleque, Md. Abdul; Tan, Chong Keng (WASET, 2012)
Particulate reinforced metal matrix composites (MMCs) are potential materials for various applications due to their advantageous of physical and mechanical properties. This paper presents a study on the performance of stir cast Al2O3 SiC reinforced metal matrix composite materials. The results indicate that the composite materials exhibit improved physical and mechanical properties, such as, low coefficient of thermal expansion, high ultimate tensile strength, high impact strength, and hardness. It has been found that with the increase of weight percentage of reinforcement particles in the aluminium metal matrix, the new material exhibits lower wear rate against abrasive wearing. Being extremely lighter than the conventional gray cast iron material, the Al-Al2O3 and Al-SiC composites could be potential green materials for applications in the automobile industry, for instance, in making car disc brake rotors. Keywords—Metal Matrix Composite, Strength to Weight Ratio, Wear Rate